2013
DOI: 10.4238/2013.december.6.3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence among accessions of melon from traditional agriculture of the Brazilian Northeast

Abstract: ABSTRACT. The genetic divergence of 38 melon accessions from traditional agriculture of the Brazilian Northeast and three commercial hybrids were evaluated using fruit descriptors and microsatellite markers. The melon germplasm belongs to the botanic varieties cantalupensis (19), momordica (7), conomon (4), and inodorus (3), and to eight genotypes that were identified only at the species level. The fruit descriptors evaluated were: number of fruits per plant (NPF), fruit mass (FM; kg), fruit longitudinal diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…In the present study, although the melon cultivars were not initially developed for cultivation in the Cerrado regions, all the melon cultivars (except the 'Hibrix' cultivar) showed feasibility for production under Cerrado conditions. The cultivars produced fruit of marketable size, and their estimated yields were over 25 tons/ha, which were in the range registered in other Brazilian regions (Aragão et al, 2013;Nunes et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, although the melon cultivars were not initially developed for cultivation in the Cerrado regions, all the melon cultivars (except the 'Hibrix' cultivar) showed feasibility for production under Cerrado conditions. The cultivars produced fruit of marketable size, and their estimated yields were over 25 tons/ha, which were in the range registered in other Brazilian regions (Aragão et al, 2013;Nunes et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Using this system, although working with the same germplasm, the groups identified by Torres Filho et al (2009) cannot be compared with the data of the present work. Similarly, Aragão et al (2013) studied the genetic diversity of accessions previously characterized by Torres Filho et al (2009), but adopted the classification of Robinson and Decker-Walters (1997), which is also very different from that used by Pitrat, Hanelt and Hammer (2000), since it considers the existence of only six varieties. The authors also observed that there was no association between morphological and molecular clusters (ARAGÃO et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Aragão et al (2013) studied the genetic diversity of accessions previously characterized by Torres Filho et al (2009), but adopted the classification of Robinson and Decker-Walters (1997), which is also very different from that used by Pitrat, Hanelt and Hammer (2000), since it considers the existence of only six varieties. The authors also observed that there was no association between morphological and molecular clusters (ARAGÃO et al, 2013). Although the information available in the Brazilian literature cannot be compared with the results achieved in this study, they invariably corroborate the existence of large variability within and among melon accessions from family farming in the state of Maranhão.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations